Some Techniques for Working with Newspapers and Newspaper Headlines in German Classes (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article is devoted to the peculiarities of using newspapers as educational material in foreign language lessons. Using the example of German-language newspaper texts, the versatility of the headline of a news text is shown as the most important structural component of teaching and learning a foreign language.